Changing roles and statuses of women in Thailand a documentary assessment - Bencha Yoddumnern; Richter, Kerry; Soonthorndhada, Amara; Sethaput, Chanya; Pramualratana, Anthony (Nakhonpathom, Thailand Institute of Population and Social Research, Mahidol University, 1992)
Contributed articles.
Framing a study of Thai women's changing roles and statuses / Kerry Richter and Brencha Yoddumnern-Attig -- Thai family structure and organization: changing roles and duties in historical perspective / Bencha Yoddumnern-Attig -- The dynamic interplay of women's roles through the life of a Northern Thai woman / George A. Attig and Bencha Yoddumnern-Attig -- The impact of societal change and role of the old in a rural community in Thailand / Anthony Pramualratana -- Adolescent role behavior, expectations and adaptations: past to present / Amara Soonthorndhada -- Domestic role behavior, expectations and adaptations: past to present / Amara Soonthorndhada -- Individual role behavior, expectations and adaptations: past to present / Amara Soonthorndhada -- Community role behavior, expectations and adaptations: past to present / Amara Soonthorndhada -- Occupational role behavior over time / Chanya Sethaput and Brencha Yoddumnern-Attig -- Integrating women in development planning: suggestions for the present and future / Chanya Sethaput -- Role strain, deprivation and conflict / Kerry Richter.
Includes bibliographical references (pages 105-106) and indexes.
Keywords: Women -- Thailand -- Social conditions